Pengaruh Kualitas Produk, Citra Merek dan Promosi terhadap Loyalitas Pelanggan pada Mie “SKR” Jember - Anggraini, Desta Rezzy; Faizah, Kurnia; Putri, Ghinadya Canceriani; Maulida, Nanda Kurniati; Qomariah, Nurul (BUDGETING : Journal of Business, Management and Accounting, 2024)
Noodles are a food product made from wheat flour without the addition of other food ingredients. Noodles are a substitute for rice which is popular with all groups, especially students. Noodle culinary delights have mushroomed under various brand names. This research aims to determine the influence of product quality, brand image and promotion on loyalty to "Mie SKR Jember". The population in this research is consumers of SKR Jember Noodles. Samples were taken using the survey method. A sample size of 30 respondents with the n ≥ 30 method is a large sample. The analysis technique used is multiple linear regression. The results of this research indicate that product quality has no impact on customer loyalty. The brand image variable has no effect on customer loyalty, while promotion has no effect on loyalty to Mie "SKR" Jember. Keywords: Brand Image; Customer Loyalty; Noodle Products; Product Quality; Promotion.